Assessing bleeding rates, related clinical impact and factor utilization in German hemophilia B patients treated with extended half-life rIX-FP compared to prior drug therapy. (2nd January 2020) - Oldenburg, Johannes; Yan, Songkai; Maro, Geraldine; Krishnarajah, Girishanthy; Tiede, Andreas
Abstract: Objective: An extended half-life factor IX (FIX) fusion protein linking recombinant FIX with recombinant human albumin (rIX-FP), indicated for the treatment of hemophilia B, was approved by the European Medicines Agency in May 2016. We aimed to compare clinical outcomes and drug utilization in patients who switched from prior FIX therapies to rIX-FP. Methods: Anonymized patient chart data were collected from German institutions treating patients with hemophilia B. Patients were included if they had been treated with rIX-FP for ≥8 weeks at the time of data collection. Bleeding rates and FIX consumption were compared between rIX-FP and patients' prior FIX products. Results: Data were obtained for 81 male patients treated with rIX-FP, including 59 who received prophylaxis with both their prior drug and rIX-FP (prophylaxis-to-prophylaxis group). Mean factor consumption in this group was 44.2 IU/kg/wk for rIX-FP compared with 82.3 IU/kg/wk for all prior FIX products. In addition, intra-patient analysis of factor consumption showed lower consumption of rIX-FP compared with prior FIX in 56 of 59 patients. Among the patients for whom bleed data were available ( n  = 42), annualized bleeding rate decreased from a mean (standard deviation) of 2.6 ± 2.9 on prior product to 0.3 ± 0.6 on rIX-FP. The proportion of patients with zero bleeds increased from 24% with prior therapy to 81% with rIX-FP. Conclusion: rIX-FP was associated with substantial reductions in bleeding rates and consumption of FIX compared with standard half-life products that require more frequent administration.